1302 Ratio of Adenoma Detection Rate to Polyp Detection Rate. (12th October 2021) - Rajain, S; Adam, A; Amarnath, T
Abstract: Introduction: Colorectal cancer is the 3 rd most common cancer in the UK. The higher Adenoma Detection Rate during colonoscopy is associated with reduction in the mortality incidence of colorectal cancer. Endoscopists with less than 20% ADR is directly proportional to higher risk of the development of an interval Colorectal cancer. The aim of this study was to calculate the Adenoma Detection Rate and Polyp Detection Rate for each endoscopist to assess the performance of the unit as well as individuals. Method: A retrospective analysis was conducted for patients who had colonoscopy in a period of 3 consecutive months at a primary care hospital in England. This study included collecting the data through patient's histology reports and medical records. The primary outcome was total Adenoma Detection Rate and Polyp Detection Rate and its ratio for each endoscopist. Results: 913 colonoscopies were done by 16 different endoscopists out of which 279 patients with polyps were considered for the study. It was observed that half of the total endoscopists were found to have ADR more than 20%. 4 endoscopists had ADR between 15-20% whereas below minimal rate (less than 15%) ADR was recorded by the other 4 endoscopists. Conclusions: Lower ADRs are associated with higher rates of interval cancers. An improvement of the ADR of 1% prevents 3% people from colon cancer which can be achieved by maintaining the aspirational adenoma detection rate more than 20%.